Treatment patterns, costs, and mortality among Medicare beneficiaries with CIED infection. Issue 5 (25th March 2018) - Greenspon, Arnold J.; Eby, Elizabeth L.; Petrilla, Allison A.; Sohail, M. Rizwan
Abstract: Background: Cardiac implantable electronic device (CIED) infection is a serious adverse event, but there are limited contemporary real‐world data on treatment pathways and associated costs in the Medicare population following diagnosis of CIED infection. Hence, this study evaluates postinfection treatment pathways and associated healthcare expenditures and mortality among Medicare fee‐for‐service beneficiaries with CIED infection. Methods: Retrospective cohort analysis of 5, 401 beneficiaries who developed a device‐related infection in the year following implantation/upgraded CIED (1/1/2010–12/31/2012). Patients were followed‐up to 12 months/death following diagnosis of infection and were divided into mutually exclusive groups based on whether they underwent CIED system removal (Group I), or no CIED system intervention (Group II; IIA with or IIB without infection hospitalization). All‐cause healthcare resource utilization/expenditures were also measured. Results: In the year following infection, 64.1% of patients underwent device extraction, of who 2, 109 (39.0%) had their device replaced (Group IA) and 1, 355 (25.1%) had their device extracted without replacement (Group IB); 62.2% of patients were hospitalized and 25.3% of patients died. Mean Medicare payments‐per‐patient for facility‐based services by group were: IA = $62, 638 (standard deviation [SD]: $46, 830), IB = $50, 079 (SD: $45, 006), IIA = $77, 397 (SD: $79, 130), and IIB = $22, 856 (SD: $31, 167). Conclusions: Hospitalizations were the largest cost driver; infection‐related costs, including cost of extraction/replacement, accounted for >50% of expenditures for patients with surgical/hospital intervention. Management of CIED infection in Medicare beneficiaries is associated with high healthcare expenditures in the year following infection. Additional measures to prevent device infection are needed to improve the outcomes and reduce costs in these patients.